Metode Role Play Basic Life Support terhadap Pengetahuan dan Keterampilan Relawan Mahasiswa - Rahmania, Annisa; Triwijayanti, Renny (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The treatment that can be done for someone with cardiac arrest is to provide basic life support. Basic Life Support (BLS) is a process related to the chain of survival. This study was to determine the effect of the basic life support role play method on the knowledge and skills of IKesT Muhammadiyah Palembang student volunteers. The method has used was the basic life support role play method on the knowledge and skills of IKesT Muhammadiyah Palembang student volunteers. The result of this study has showed that knowledge had a p value of 0.001 (p value ≤ 0.05), and attitudes had a p value of 0.001 (p value ≤ 0.05). The conclusion of this study is There is an influence on the knowledge and skills of student volunteers before and after being given the BLS Role Play with a p value of 0.001 <0.05. Keywords: Basic Life Support, Student Volunteers, Role Play